The rise of the green economy. A new paradigm for the developing world? - (:unkn) unknown (oekom, 2019)
The need to achieve a green economy has recently gained more and more attention. International organisations, governments and representatives from civil society and the private sector have put forward suggestions for a successful transition to a green and low-carbon economy. Around the world, a patchwork of local, regional and national green economy strategies has developed. This is also due to the UN Conference on Sustainable Development in 2012, "Rio+20", which built up momentum in the discourse surrounding transition to a green economy. The outcome encourages countries to build a common understanding of how economic policy can commit to sustainable development and eradication of poverty. With conceptual reflections on the status of the green economy discourse and with insights from numerous country case studies, this book aims at offering some guidance on this important area for global environmental and development governance.
Keywords: Wirtschaft; Wirtschaftsentwicklung; Entwicklungsziel; Ökologie; Nachhaltigkeit; Internationaler Vergleich; Green economy